Chronic stress experience, sleep, and physical activity: Relations with change in negative affect and acute stress response to a naturalistic stressor. Issue 2 (22nd August 2021) - Nordberg, Hannah; Kroll, Juliet L.; Rosenfield, David; Chmielewski, Michael; Ritz, Thomas
Abstract : Objectives: Prior research indicates that chronic stress increases allostatic load and alters individuals' affective response to stress. Recent studies have linked health‐related behaviours including poor sleep and physical inactivity with elevated negative affect responses to stress. This study extends prior work to investigate chronic stress experience, sleep, and physical activity as predictors of negative affect and acute stress experience during acute, sustained naturalistic stress. Design: Students ( N  = 637) were assessed during an academic semester and end‐of‐term final exam period. Methods: Self‐report ratings of chronic stress experience, negative affect, acute stress experience, sleep, physical activity, demographics, and health were obtained. Hierarchical multiple regression analyses examined the extent to which chronic stress experience, sleep duration and sleep quality, habitual physical activity, and their interactions, predicted changes in negative affect and acute stress experience during final exams. Health‐related behaviours were also examined as mediators between chronic stress experience and changes in negative affect and acute stress experience. Results: Greater chronic stress experience and shorter exam period sleep duration, but not habitual sleep duration or physical activity, predicted greater increases in negative affect and acute stress experience. Poorer overall sleep quality was a significant predictor in these models and partially mediated the relation between chronic stress experience and negative affect and acute stress experience. Conclusions: Findings highlight the importance of chronic stress experience and sleep in predicting individuals' affective health during naturalistic stress. Interventions that reduce chronic stress experience and improve sleep may help individuals' buffer against impairments to affective health during these episodes.